DOES HEURISTIC BEHAVIOR LEAVE ANOMALIES IN THE CAPITAL MARKET? - Shafiera Lazuarni; Prof. Marwan Asri, M.B.A., Ph.D. (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction/Main Objectives: This study aims to examine the role of heuristic behavior toward the formation of fundamental and technical anomalies in the capital market. This study also aims to examine the role of fundamental and technical anomalies on investment performance. Background Problems: Efficient Market Hypothesis (EMH) is not always able to explain all of the events or phenomena so that it still raises questions and produces research results that do not meet expectations, so in the end these phenomena are categorized as market anomalies. This study investigates whether heuristics have an effect on fundamental and technical anomalies and whether the anomalies have an effect on investment performance. Novelty: There is no research that uses hindsight variables incorporated into heuristics; therefore, this study confirms that the indicators used for hindsight measurements are appropriate for measuring what will be measured. Previous research did not involve hindsight in the heuristic category. Research Methods: Data management are done by using Structural Equation Modelling (SEM) with the help of the WarpPLS analysis tool. Mediation exploration testing was accomplished with variance accounted for (VAF). Findings/Results: The results of the study show that heuristics (availability, representativeness, and hindsight) are proven to be one of the factors that cause fundamental and technical anomalies in the capital market, except for availability heuristics. Conclusion: A large number of anomalies in the capital market do not stop investors from continuing to invest, so that at a certain level, investors are satisfied with their investments’ performance because they use heuristics in an efficient way.